Thyroid Regeneration: How Stem Cells Play a Role? - Kimura, Shioko (Frontiers in Endocrinology, 2014)
Many tissues if not all are thought to contain stem cells that are responsible for regeneration and repair of the tissue after injury. Dysregulation of tissue regeneration may result in various pathological conditions, among which cancer is the most extensively studied. Notably, the so called cancer stem cells or tumor-initiating cells, have been studied in order to understand the mechanisms of carcinogenesis and/or metastasis. However, the nature of cancer stem cells, let alone normal stem/progenitor cells, particularly those of the thyroid remains elusive. There remains a gap in knowledge between adult thyroid stem/progenitor cells and cancer stem cells of the thyroid, and if and/or how they are related to each other. Understanding of the mechanism for thyroid regeneration and mode of participation of normal adult thyroid stem/progenitor cells in this process will hopefully yield a more complete understanding of the nature of thyroid cancer stem cells, and/or help understand the pathogenesis of other thyroid diseases. This review summarizes the current understanding of adult thyroid stem/progenitor cells, with particular emphasis on how they contribute to thyroid regeneration.